2016
DOI: 10.1088/2040-8978/19/1/014002
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral photoacoustic imaging of tumours in mice injected with an enzyme-activatable photoacoustic probe

Abstract: Photoacoustic (PA) imaging offers depth-resolved images of optical absorbers with the spatial resolution of ultrasound imaging. To enhance tumour contrast, tumour-specific probes are used as contrast agents. We synthesised a colourless PA probe that is activated in the presence of γ-glutamyltranspeptidase, a cancer-associated enzyme, to show its original colour and fluorescence. We have acquired high specificity fluorescence images of small tumours, using a fluorescent probe based on similar enzymatic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The motorized stage, digital oscilloscope, light source, and analog counter were synchronized with a LabVIEW program. The PA signals were enveloped using the Hilbert transform to calculate the intensities [39] . Image distortion because of fluctuation in the stage translation speed was compensated using a linear gauge.…”
Section: Methodsmentioning
confidence: 99%
“…The motorized stage, digital oscilloscope, light source, and analog counter were synchronized with a LabVIEW program. The PA signals were enveloped using the Hilbert transform to calculate the intensities [39] . Image distortion because of fluctuation in the stage translation speed was compensated using a linear gauge.…”
Section: Methodsmentioning
confidence: 99%
“…, light illumination) [36, 74] or internally ( e.g. , chemical cleavage) [75, 76, 83]. For example, several groups (including the authors’) have explored the reversible photoswitching capability of several fluorescent (Dronpa, rsTagRFP) and non-fluorescent (BphP1, AGP1) proteins [36, 74, 84].…”
Section: Advances In Signal Unmixing Methodsmentioning
confidence: 99%
“…The tumor is a type of disease in the vascular system that can also lead to stroke. Many studies on PAI for tumor imaging have shown good performance [ [99] , [100] , [101] , [102] , [103] ]. Furthermore, a peripheral vascular system disease can influence the cerebrovascular system and lead to the occurrence of stroke [ 104 ].…”
Section: Photoacoustic Imaging For Strokementioning
confidence: 99%